Supermarket - Azuchi, Satoshi 1937-; Warham, Paul. (New York Thomas Dunne Books, 2009)
After he resigns from his elite banking job to help a cousin manage a supermarket in post-World War II Japan, Kojima is challenged by a woman from his childhood to consider whether his business goals are worth his efforts.
"Previously published in Japan as Shosetsu supamaketto by Kodansha Co. Ltd., Tokyo"--Title page verso.
Keywords: Supermarkets -- Japan -- Fiction; Supermarkets -- Japan -- Management -- Fiction; Bankers -- Japan -- Fiction; Success in business -- Fiction; Japan -- Social conditions -- Fiction; Japan -- Economic conditions -- Fiction